2016
DOI: 10.1186/s40064-016-3497-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing rock phosphate integration rate for fast bio-transformation of cow-dung waste-paper mixtures to organic fertilizer

Abstract: Rock phosphate (RP) addition in cow-dung waste-paper mixtures at rates above 2% P has been reported to increase the rate of bio-transformation and humification of organic waste mixtures during vermicomposting to produce organic fertilizer for organic farming. However, the optimization of RP for vermicomposting was not established. The objective of this study was to determine the optimal amount of RP integration rates for effective bio-transformation of cow-dung waste-paper mixtures. Arrays of RP integration de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…Thus, SEM images in this study were similar to that of (Lim et al 2015(Lim et al , 2016, and it reveals that increase in the decomposition of the mixtures significantly depends on time. The wider contrasts in the degree of decomposition observed from various treatments at 14th and 28th days agreed with the time of most extreme microbial action (Unuofin et al 2016). < 0.001 < 0.001 < 0.001 < 0.001 < 0.001 < 0.001 < 0.001 < 0.001 < 0.001…”
Section: Morphology Of Vermicompost Revealed By Scanning Electron Micsupporting
confidence: 69%
See 2 more Smart Citations
“…Thus, SEM images in this study were similar to that of (Lim et al 2015(Lim et al , 2016, and it reveals that increase in the decomposition of the mixtures significantly depends on time. The wider contrasts in the degree of decomposition observed from various treatments at 14th and 28th days agreed with the time of most extreme microbial action (Unuofin et al 2016). < 0.001 < 0.001 < 0.001 < 0.001 < 0.001 < 0.001 < 0.001 < 0.001 < 0.001…”
Section: Morphology Of Vermicompost Revealed By Scanning Electron Micsupporting
confidence: 69%
“…Rock phosphate (RP), Triple superphosphate (TSP), Phosphoric acid (PHA) and calcium chloride (CaCl 2 ) were the treatments used. The P-source treatments were inoculated into the waste mixtures at 1%, P since this gave the ideal rate of RP application that brought about speediest decomposition of the waste mixtures (Unuofin et al 2016). Calcium chloride was also applied to the mixtures at the level of Ca supplied by RP when applied at 1% P. A control (with earthworm yet no P sources) was included.…”
Section: Experimental Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed GI is a direct indicator of residue or compost toxicity (Phoungthong et al, 2016) because it directly establishes if the residues can inhibit plant growth when used as soil amendment or as a direct means of growth. A GI greater than 80%, observed for all the treatments in the present study, indicated that pellets mixed with a degraded Alfisol would have phytotoxin or heavy metal levels that do not affect plant growth (Unuofin et al, 2016); instead, evaluated indices increased as indicated by the radish seed germination tests. Agricultural application of pellets of ash and sludge may be limited by their phytotoxic effect during seedling establishment, which was assessed using the Germination Index (GI).…”
Section: Radish Seed Germination Experiments In Extracts Ofmentioning
confidence: 47%
“…Phytotoxicity was determined by GI as suggested by Tiquia and Tam (1998), allowing the evaluation of the low or minor toxicity that affects root growth, as well as the high or major toxicity (Nafez et al, 2015;Unuofin et al, 2016), to determine the effect on radish seed germination, as expressed in equation 1:…”
Section: Phytotoxicity Experiments With Radish Seedsmentioning
confidence: 99%